Interest-Based Career Guidance Strategies to Improve the Employability of People with Disabilities: Systematic Literature Review - Pardi; Dede Rahmat Hidayat; Aip Badrujaman (Universitas PGRI Yogyakarta, 2025)
People with disabilities often face significant challenges in accessing equal employment opportunities, with unemployment rates remaining relatively high. Interest-based career guidance is a potential strategy to address this issue, as this approach assumes an individual’s abilities, interests, and aspirations. This research uses the Systematic Literature Review (SLR) method to identify interest-based career guidance strategies that effectively improve the employability skills of people with disabilities and analyse the supporting and inhibiting factors in their implementation. The results show that interest-based, personalised approaches and multidisciplinary support can improve the employability skills and integration of people with disabilities into the world of work. Enabling factors such as social support, inclusive awareness, and multisector collaboration are crucial, while barriers such as stigma, lack of resources, and inadequate policies need to be addressed. This research provides practical recommendations for policymakers, educators, and practitioners to optimise interest-based career guidance programmes for people with disabilities. Keywords: career guidance, people with disabilities, job skills, interests, inclusion